Welfare implication of paddy price support withdrawal from Malaysian rice sector: partial equilibrium method approach - Umar, Haruna Suleiman; Abdullah, Amin Mahir; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin (De Gruyter Open, 2015)
The study was designed to analyze societal welfare implication of paddy price support withdrawal, as an alternative policy, from rice sector in Malaysia. Time series data (1980-2012) were collected and analyzed through different stages of analyses. The first stage of analysis involved time series econometric model namely, Auto Regressive Distributed Lag (ARDL), which was used in coefficients estimation. Estimated coefficients were subjected to, and passed the relevant diagnostic tests. The estimated elasticities were then used for the second stage of analysis- scenario simulation. Finally, the generated simulation results were further used in estimating the societal welfare changed through appropriate estimation technique. Results show producer welfare loss of about RM189 million, and RM198 million was saved as revenue. The net gain or societal welfare improvement was about RM9 million. Simulated results show up to 10% reduction in paddy producer price or farm income; this could serve as disincentive to rice producers. Since the country is concerned about achieving rice self-sufficiency and rice food security, necessary precautionary measures have to be instituted to prevent farmers exit from paddy farming, by putting a concerted effort towards channeling the trickle-down benefit of societal welfare improvement, resulting from policy option, to rice producers particularly the dominant smallholder group.